Relationship of Dental Caries with Quality of Life in Early Childhood - Ismalayani Ismalayani (Humanistic Network for Science and Technology (HNST), 2022)
Quality of life is a person's ability to enjoy normal life activities. Healthy living is part of the quality of life, because it is healthy not only physically but also mentally and socially healthy. Oral health is an inseparable part of general health because dental and oral health conditions can affect daily life. The aim of the study was to determine the relationship between dental caries and quality of life in early childhood. A cross sectional study conducted in February 2021at PAUD Baiturrohim Palembang. Sample consisted of 67 children and their mothers taken by purposive sampling. Dental caries status was measured using the def-t index and children's quality of life was measured using the Early Childhood Oral Health Impact Scale (ECOHIS). Data were analyzed using the Chi-square test with a 95% confidence interval. Most children have very high def-t category criteria (56.7%) and bad category in quality of life (53.7%). The bivariate analysis was found the significant relationship between dental caries and quality of life (p <0.05), so it can be concluded that dental caries can reduce the quality of life. It is hoped that it can become an insight for the community, especially mothers as the main pillar of children's dental and oral health, in a strategic effort to prevent early caries based on community empowerment through the Innovative UKGTK and Innovative UKGS programs for early childhood in Palembang City. Keywords: dental caries; def-t; quality of life; ECOHIS; early childhood